The Profile of Scientific Literacy Skill Student at SMA Batik 2 Surakarta - Shofwan Ridho; Nonoh Siti Aminah; Agus Supriyanto (Universitas Negeri Jakarta, 2018)
Some research showed that many teachers have literacy skills but they have not used them in the classroom yet.This research aims to describe science literacy competence of SMA Batik 2 Surakarta students and teacher. The research uses qualitative descriptive method. The study was conducted at SMA Batik 2 Surakarta with tenth grade science class students as the subjects. There were 88 students as and 2 teacher  the subjects. The samples selected by using total sampling technique. The research instrument used in this study is science literacy test adapted from PISA (Programme for International Student Assesment). The data analysis technique used is percentage. The result of this study shows that 57,41% student mastered the science literacy competence, the student completed in science literacy competence included in the middle level this research. The interviews with teachers and students show that the use of science literacy in the classroom is still low.This research is complementary the study of the importance of teacher ability analysis in the use of scientific literacy skill in the classroom